Penggunaan Media Pembelajaran Microsoft Sway untuk Meningkatkan Proses dan Hasil Belajar IPAS Siswa Kelas IV SDN Munggut 01 Madiun - Nurma Fitri Handayani; Sri Endang Maruti; Suprihatin Suprihatin (Populer: Jurnal Penelitian Mahasiswa, 2024)
This study aims to determine the improvement of the quality of the process and results of learning the material me and my needs of class IV SDN Munggut 01 through the use of Microsoft Sway learning media. This study was conducted because of the low interest in learning and the learning outcomes of students who did not reach the maximum in the subject of science for class IV material me and my needs. The cause of the low interest in learning and learning outcomes is because the teacher does not use more effective learning media. This study is a Classroom Action Research (CAR) consisting of two cycles. The findings of the study indicate that the use of Microsoft Sway website-based media can improve the process and learning outcomes of class IV students of SDN Munggut 01. This increase can be seen from the learning outcomes in cycle I to cycle II, as well as the increase in the value of learning completeness classically, where in cycle I it only reached 33.33% while in cycle II it increased to 86.66%. Microsoft Sway media in class IV SDN Munggut 01 can improve students' ability to understand the material and improve learning outcomes.